Regulation of Osteoclast Multinucleation by the Actin Cytoskeleton Signaling Network. Issue 2 (February 2015) - Takito, Jiro; Otsuka, Hirotada; Yanagisawa, Nobuaki; Arai, Hiroshi; Shiga, Masayasu; Inoue, Mitsuko; Nonaka, Naoko; Nakamura, Masanori
<x xml:space="preserve">Abstract</x> Although it is known that osteoclasts are multinucleated cells that are responsible for bone resorption, the mechanism by which their size is regulated is unclear. We previously reported that an actin‐rich superstructure, termed the zipper‐like structure, specifically appears during the fusion of large osteoclast‐like cells (OCLs). Actin cytoskeleton reorganization in osteoclasts is regulated by a signaling network that includes the macrophage colony‐stimulating factor (M‐CSF) receptor, a proto‐oncogene, Src, and small GTPases. Here, we examined the role of actin reorganization in the multinucleation of OCLs differentiated from RAW 264.7 cells using various pharmacological agents. Jasplakinolide, which stabilizes actin stress fibers, induced the development of small OCLs, and the Src inhibitor SU6656 and the dynamin inhibitor dynasore impaired the maintenance of the podosome belt and the zipper‐like structure. These inhibitors decreased the formation of large OCLs but increased the number of small OCLs. M‐CSF is known to stimulate osteoclast fusion. M‐CSF signaling via Src up‐regulated Rac1 activity but down‐regulated Rho activity. Rac1 and Rho localized to the center of the zipper‐like structure. Rho activator II promoted the formation of small OCLs, whereas the Rho inhibitor Y27632 promoted the generation of large OCLs. These results suggest that the status of the actin cytoskeleton signaling network determines the size of OCLs during cell fusion. J. Cell. Physiol. 230: 395–405, 2015. © 2014 Wiley Periodicals, Inc.